2018
DOI: 10.1111/pai.12971
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ and innate immune pathways are activated and differentially expressed in childhood asthma phenotypes

Abstract: Ca regulation and innate immunity response pattern to viruses were activated in PBMCs of asthmatics. Asthma phenotypes were differentially characterized by distinct regulation of ATP2A3 and expression of innate immune receptors (FPR2, CLEC4E, IFIH1). These genes may present promising targets for future in-depth investigation with the long-term goal of more phenotype-specific therapeutic interventions in asthmatics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…FPR2 is a unique G-protein-coupled receptor, which is critical to the resolution of inflammation (Cooray et al, 2013). Previous studies have reported that Anxa1 and FPR2 play an important role in the pathogenesis of asthma (Perucci et al, 2017;Boeck et al, 2018;Lee et al, 2018). Anxa1 can reduce inflammation by regulating neutrophil transmigration, promoting neutrophil apoptosis and efferocytosis, inducing tissue repair, and recruiting monocytes (Maderna et al, 2005;Vago et al, 2012;Sugimoto et al, 2019;Machado et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…FPR2 is a unique G-protein-coupled receptor, which is critical to the resolution of inflammation (Cooray et al, 2013). Previous studies have reported that Anxa1 and FPR2 play an important role in the pathogenesis of asthma (Perucci et al, 2017;Boeck et al, 2018;Lee et al, 2018). Anxa1 can reduce inflammation by regulating neutrophil transmigration, promoting neutrophil apoptosis and efferocytosis, inducing tissue repair, and recruiting monocytes (Maderna et al, 2005;Vago et al, 2012;Sugimoto et al, 2019;Machado et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Among the variants investigated, the asthma-increasing risk allele rs2305480*G is associated with the down-regulation of GSDMB , ORMDL3 , and PGAP3 and the up-regulation of GSDMA and IKZF3 across multiple tissues. Accordingly, we can hypothesize that the effect of rs2305480 on asthma risk and the blood levels of immune cells is due to mechanisms related to the function of multiple genes, including the GSDMB and GSDMA regulation of apoptosis in epithelial cells, 33 34 ORMDL3 regulation of the innate immune system, 35 and IKZF3 regulation of B lymphocyte proliferation and differentiation. 36 37 Among the other variants tested, the asthma-increasing risk rs1558641*G allele was associated with the up-regulation of MFSD9 and down-regulation of IL18R1 .…”
Section: Discussionmentioning
confidence: 99%
“…12 This publication adds additional insights into the mechanisms of asthma. Readers with a special research interest in the field might also refer to these recent original publications in PAI [13][14][15] or to a recent review on oxidative stress and asthma. 16 Eila Kujansuu Jinpao Hou (le[) and Jennifer Wing-Ki Yau (right) Jonatan Leffler (le[) and James F. Read (right)…”
mentioning
confidence: 99%
“…This publication adds additional insights into the mechanisms of asthma. Readers with a special research interest in the field might also refer to these recent original publications in PAI or to a recent review on oxidative stress and asthma …”
mentioning
confidence: 99%